2007
DOI: 10.1080/00016340701505044
|View full text |Cite
|
Sign up to set email alerts
|

Low predictive value of traditional risk factors in identifying women at risk for gestational diabetes

Abstract: Selective screening based on traditional risk factors for GDM had relatively low sensitivity, and identified <60% of Caucasian women at risk. The cut-off value for BMI as a risk indicator (23 kg/m2) was lower than that proposed by guidelines about screening for GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Our approach was similar to that of several studies designed with the aim to identify the best diagnostic approach for GDM (19,20,21,22,23). In the European countries, the nonconformity of screening and diagnostic procedures for GDM is responsible for the different reported prevalence rates of GDM (6).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our approach was similar to that of several studies designed with the aim to identify the best diagnostic approach for GDM (19,20,21,22,23). In the European countries, the nonconformity of screening and diagnostic procedures for GDM is responsible for the different reported prevalence rates of GDM (6).…”
Section: Discussionmentioning
confidence: 80%
“…However, it is widely accepted that previous GDM is one of the best predictors of GDM, as reported in many studies (22). Furthermore, the lack of information on the maternal and fetal outcomes did not allow us to assess the predictive role of individual RFs for GDM in the occurrence of these outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although many studies have reported the risk factors for GDM, [9][10][11][12][13][14] to our knowledge only a few studies have integrated patient characteristics and medical history in a quantitative manner by means of a risk scoring system or a prediction model. [15][16][17] In this article, we developed a multivariable logistic regression model in which we combined patient characteristics and medical history to predict the occurrence of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic T a b l e 1 . P l a s ma Gl u c o s e Va l u e s d u r i n g GCT a n d OGT T i n P r e g n a n t Wo me n criteria for the 100-g (12). Glycosuria is also a poor predictor of GDM to be considered effective as a screening tool (and this pre-screening test does not seem to identify) GDM (13).…”
Section: Gestational Diabetes Mellitus (Gdm) Is Defined As Any Degreementioning
confidence: 99%